Analysis the Effect of Learning Organization, Communication Skill, and Compensation on Funding Officer Employee Performance with Motivation as an Intervening Variable (Study on E-Channel Marketing at PT. Bank Rakyat Indonesia Agroniaga, Tbk) - Thea Geneveva Ahmad Shalahuddin M. Irfani Hendri (Equator Journal of Management and Entrepreneurship (EJME), 2021)
The purpose of this study is to see whether there is a significant influence between the variables of learning organization, communication skills, and compensation on performance through motivational variable as intervening variable which conducted at PT Bank Rakyat Indonesia Agroniaga, Tbk. This study uses quantitative research methods with data collection through the distribution of questionnaires and interviews (discussions) to employee as a respondent at PT Bank Rakyat Indonesia Agroniaga, Tbk. The results showed that learning organization, communication skills, and compensation had a significant positive effect on employees' work motivation. Furthermore, learning organization had a significant positive effect on employee performance, while communication skills and compensation had no significant effect on employee performance. The results of the Sobel Test showed that the motivation variable did not succeed in mediating the learning organization, communication skill, and compensation variables. Keywords: learning organization, communication skill, compensation, motivation, performance.